The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1510/icvts.2009.208835
|View full text |Cite
|
Sign up to set email alerts
|

Circulating matrix metalloproteinase-9 concentrations and abdominal aortic aneurysm presence: a meta-analysis

Abstract: To summarize the present evidence for an association between matrix metalloproteinase-9 (MMP-9) and abdominal aortic aneurysm (AAA) presence, we performed a meta-analysis of case-control studies that compared circulating MMP-9 concentrations between patients with AAA and subjects without AAA. MEDLINE database was searched to identify all case-control studies. For each study, data regarding serum or plasma MMP-9 concentrations in both the AAA and control groups were used to generate standardized mean difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 13 publications
1
36
0
2
Order By: Relevance
“…Numerous molecules including MMPs, C-reactive protein (CRP) and D-Dimer have shown promise in the prediction of acute aortic dissection. 13 A recent meta-analysis implicated measurement of circulating MMP-9 as an indicator of abdominal aortic aneurysm (AAA) disease, 14 and plasma measurement of MMP-1 and MMP-9 has been shown to be predictive of aortic rupture. 15 Further, composite measurement of high density lipoprotein (HDL), CRP and immunoglobulin G correlates to AAA size.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous molecules including MMPs, C-reactive protein (CRP) and D-Dimer have shown promise in the prediction of acute aortic dissection. 13 A recent meta-analysis implicated measurement of circulating MMP-9 as an indicator of abdominal aortic aneurysm (AAA) disease, 14 and plasma measurement of MMP-1 and MMP-9 has been shown to be predictive of aortic rupture. 15 Further, composite measurement of high density lipoprotein (HDL), CRP and immunoglobulin G correlates to AAA size.…”
Section: Discussionmentioning
confidence: 99%
“…The level of circulating MMP-9 was significantly higher in patients with AAA than in those without AAA. Moreover, recent study reported that the level of MMP-9 in the plasma was statistically elevated in patients with ruptured AAA, compared to patients with nonruptured AAA [19]. Strikingly, it was reported that the inhibition of MMP activity prevented the development of AAA.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs are involved in flow-induced outward vascular remodeling 122 and several aspects of cardiovascular remodeling, e.g., left ventricular hypertrophy, atherosclerosis, and/or aortic aneurysm. [123][124][125] Several studies on CKD patients showed serum-level variations of MMPs and their inhibitors. 126,127 Arterial enlargement, arterial stiffening, and increased circumferential wall stress occurred in parallel with GFR decline, but their relative importance is more complex.…”
Section: Arterial Remodeling and Stiffness In Ckd Stages 2-5mentioning
confidence: 99%